2018
DOI: 10.1007/s00384-018-3191-7
|View full text |Cite
|
Sign up to set email alerts
|

Sex- and site-specific differences in colorectal cancer risk among people with type 2 diabetes

Abstract: PurposeThe prevalence of colorectal cancer is higher among patients with type 2 diabetes mellitus (T2D) than among patients without diabetes. Furthermore, men are at higher risk for developing colorectal cancer than women in the general population and also subsite-specific risks differ per sex. The aim was to evaluate the impact of T2D on these associations.MethodsA population-based matched cohort study was performed using data from the PHARMO Database Network. Patients with T2D were selected and matched (1:4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 29 publications
(51 reference statements)
3
19
0
3
Order By: Relevance
“…Statin users had a decreased risk of colorectal cancer compared with nonstatin users ( 13 ). Patients with diabetes, consistent with Overbeek et al ( 22 ), have an increased risk of developing colorectal cancer; however, the study did not account for smoking status nor BMI in estimating models as we did. Unlike Mamtani et al, we found an increased total serum cholesterol to be associated with an increased hazard of colorectal cancer similar to another study ( 13 , 23 ).…”
Section: Discussionsupporting
confidence: 65%
“…Statin users had a decreased risk of colorectal cancer compared with nonstatin users ( 13 ). Patients with diabetes, consistent with Overbeek et al ( 22 ), have an increased risk of developing colorectal cancer; however, the study did not account for smoking status nor BMI in estimating models as we did. Unlike Mamtani et al, we found an increased total serum cholesterol to be associated with an increased hazard of colorectal cancer similar to another study ( 13 , 23 ).…”
Section: Discussionsupporting
confidence: 65%
“…Site-speci c difference of CRC risk among people with T2DM has been reported previously [22]. TP53 mutation was observed in distal colon and rectal tumors at higher frequencies, while it was observed in proximal tumors at lower frequencies [23].…”
Section: Discussionsupporting
confidence: 58%
“…While the mediating factors for this sex difference need further study (e.g., history of GDM, which was outside of the scope of this review), the increased prevalence of diabetes among women in some LatAm countries would be expected to have implications for health and health care, and potentially future generations [ 267 – 269 ]. Since diabetes may increase women’s risk for CVD, including stroke [ 270 ], cognitive decline [ 271 , 272 ], or some cancers [ 273 , 274 ], timely and comprehensive preventive care for women of all ages would need to be prioritized.…”
Section: Additional Observationsmentioning
confidence: 99%